Examining Patriotism Between Multiculturalism and Ethnoculturalism - Mansurni Abadi; Putu Ayu Suniadewi (CV. Austronesia Akademika, 2025)
Patriotism, as a form of collective loyalty to the nation, is a complex phenomenon shaped by competing cultural and philosophical frameworks. Contemporary debates often contrast multiculturalist perspectives, which promote inclusivity and civic values, with ethnoculturalist views that emphasize homogeneity rooted in ethnicity, language, or cultural heritage. This study aims to examine patriotism within these contrasting paradigms and to explore their implications for national identity, social cohesion, and political life. Employing a systematic literature review (SLR) methodology, the research synthesizes theoretical insights from anthropology, sociology, political science, and philosophy. The analysis highlights that multiculturalist approaches view patriotism as inclusive, fostering unity through diversity and shared civic responsibility, while ethnoculturalist perspectives tend to reinforce exclusivity, privileging dominant cultural groups and marginalizing minorities. Findings further reveal that extreme forms of cosmopolitanism and nationalism each pose challenges, potentially weakening cohesion by drawing citizens toward polarized positions. Between these poles, patriotism is understood as a socially constructed sentiment mediated by rituals, symbols, and collective memory, requiring both integrity and responsibility. The study concludes that a balanced form of patriotism integrating civic values with cultural recognition offers a more sustainable framework for pluralistic societies. By navigating between multiculturalism and ethnoculturalism, this research underscores the importance of moderation in cultivating national solidarity without erasing cultural differences.